The genome of the endophytic bacterium H. frisingense GSF30T identifies diverse strategies in the Herbaspirillum genus to interact with plants - Straub, Daniel; Rothballer, Michael; Hartmann, Anton; Ludewig, Uwe (Frontiers in Microbiology, 2013)
The diazotrophic, bacterial endophyte Herbaspirillum frisingense GSF30T has been identified in biomass grasses grown in temperate climate, including the highly nitrogen-efficient grass Miscanthus. Its genome was annotated and compared with related Herbaspirillum species from diverse habitats, including H. seropedicae, and further well-characterized endophytes. The analysis revealed that Herbaspirillum frisingense lacks a type III secretion system that is present in some related Herbaspirillum grass endophytes. Together with the lack of components of the type II secretion system, the genomic inventory indicates distinct interaction scenarios of endophytic Herbaspirillum strains with plants. Differences in respiration, carbon, nitrogen and cell wall metabolism among Herbaspirillum isolates partially correlate with their different habitats. Herbaspirillum frisingense is closely related to strains isolated from the rhizosphere of phragmites and from well water, but these lack nitrogen fixation and metabolism genes. Within grass endophytes, the high diversity in their genomic inventory suggests that even individual plant species provide distinct, highly diverse metabolic niches for successful endophyte-plant associations.